Study on the acceptability of the food bar from tongka langit banana (Musa troglodytarum) with addition of walnuts - Nurul F Leko; Vita N Lawalata; Gilian Tetelepta (Universitas Pattimura, 2022)
The objective of this study was to analyze the acceptability of the food bar from tongka langit banana with the addition of walnuts through testing organoleptic properties, a completely randomized experimental design with one factor replicated twice was applied with treatment was a concentrate of walnuts 0%, 5%, 10%, and 15%. The organoleptic tested were color, aroma, taste, and texture using the hedonic test, hedonic quality test, and plural comparison tests. The results showed that the tongka langit banana food bar with a walnut concentration of 15% had the best level of acceptance with a hedonic value of 2.8 scent color 2.72, taste 2.7, texture 2.8 which all included criteria approaching the hedonic quality value of color 2.4 (slightly yellow), aroma 2.75 (close to a banana-scented), taste 2.65 (close to hard), plural color values of 2.12 (slightly yellow from R) aroma of 3.5 (the same is good), 2.95 taste (close to better) and 2.35 texture (a bit hard) compared to commercial food bar soyjoy banana (R).